Bioimpedance cardiography in pregnancy: A longitudinal cohort study on hemodynamic pattern and outcome. Issue 1 (December 2016) - Andreas, Martin; Kuessel, Lorenz; Kastl, Stefan; Wirth, Stefan; Gruber, Kathrin; Rhomberg, Franziska; Gomari-Grisar, Fatemeh; Franz, Maximilian; Zeisler, Harald; Gottsauner-Wolf, Michael
Abstract Background Pregnancy associated cardiovascular pathologies have a significant impact on outcome for mother and child. Bioimpedance cardiography may provide additional outcome-relevant information early in pregnancy and may also be used as a predictive instrument for pregnancy-associated diseases. Methods We performed a prospective longitudinal cohort trial in an outpatient setting and included 242 pregnant women. Cardiac output and concomitant hemodynamic data were recorded from 11th –13th week of gestation every 5th week as well as at two occasions post partum employing bioimpedance cardiography. Results Cardiac output increased during pregnancy and peaked early in the third trimester. A higher heart rate and a decreased systemic vascular resistance were accountable for the observed changes. Women who had a pregnancy-associated disease during a previous pregnancy or developed hypertension or preeclampsia had a significantly increased cardiac output early in pregnancy. Furthermore, an effect of cardiac output on birthweight was found in healthy pregnancies and could be confirmed with multiple linear regression analysis. Conclusions Cardiovascular adaptation during pregnancy is characterized by distinct pattern described herein. These may be altered in women at risk for preeclampsia or reduced birthweigth. The assessment of cardiac parameters by bioimpedance cardiography could be performed at low costs without additional risks.